Optimizing employee attraction and retention in hospitality and tourism: A systematic review of employer branding research - Kilson, Gabriel Almeida (Administrative sciences, 2025)
The hospitality and tourism (H&T) sector, marked by intense employee-customer interactions, dynamic labor shifts, and high physical and emotional labor demands, faces chronic talent acquisition and retention. Therefore, tailored employer branding (EB) strategies that address the unique characteristics of the H&T sector are essential for improving the current situation. Despite the critical need for tailored solutions, a clear and unified approach for H&T companies to effectively manage their EB strategies, including the development of a compelling employee value proposition (EVP) that resonates with targeted professionals, has yet to be established. Following the PRISMA reporting guidelines, a systematic literature review of 30 peer-reviewed articles from the Scopus and Web of Science databases was conducted to synthesize existing research on EB practices in the H&T sector. The results reveal a fragmented literature that lacks a cohesive framework for categorizing and measuring EVP. The use of varied and inconsistent EVP models and scales across studies hampers comparative analysis and limits the development of generalizable insights. Furthermore, the review highlights a concentration of research within the hotel industry, leaving other important H&T industries, such as the restaurant and cruise industries, underexplored. This SLR emphasizes the urgent need for a unified approach to EB in H&T. Based on these results, promising research avenues are suggested to further advance EB research in H&T, along with managerial implications for enhancing talent attraction and retention in the sector.